Conservative finite difference methods for fractional Schrödinger–Boussinesq equations and convergence analysis. Issue 4 (13th January 2019) - Liao, Feng; Zhang, Luming; Hu, Xiuling
Abstract : In this paper, two conservative finite difference schemes for fractional Schrödinger–Boussinesq equations are formulated and investigated. The convergence of the nonlinear fully implicit scheme is established via discrete energy method, while the linear semi‐implicit scheme is analyzed by means of mathematical induction method. Our schemes are proved to preserve the total mass and energy in discrete level. The numerical results are given to confirm the theoretical analysis.